Hyaluronic acid methacrylate/laponite hydrogel loaded with BMP4 and maintaining its bioactivity for scar-free wound healing. (22nd March 2023) - Chang, Likun; Xu, Yulong; Wu, Zhouying; Shao, Yichun; Yu, Dan; Yang, Wenyue; Ye, Liyuan; Wang, Xinyu; Li, Binbin; Yin, Yixia
Abstract: Scar-free wound healing is a challenging process due to the excessive deposition of extracellular matrix and collagen. To overcome this issue, hydrogels with superior biochemical and mechanical properties have been used in combination with medicinal compounds as wound dressings. In this study, a novel composite hydrogel consisting of double-crosslinked photocurable hyaluronic acid methacrylate (HAMA) and Laponite (Lap) loaded with bioactive bone morphogenetic protein 4 (BMP4) was developed and thoroughly characterized for its properties such as degradation, morphology, porosity, compression, skin adhesion and load release. The effect of the HAMA/Lap/BMP4 hydrogel was evaluated through both in vitro and in vivo experiments. In the in vivo rabbit ear-scar model, the HAMA/Lap/BMP4 hydrogel dressing was found to reduce scar-related expressions of α-SAM and decrease the ratio of collagen Ι/III in wounded tissue. Additionally, histopathological examination indicated that the HAMA/Lap/BMP4 hydrogel-treated groups exhibited enhanced wound repair and increased levels of collagen maintenance compared to other standard groups, ultimately leading to scarless wound healing. Therefore, this sustained-release photocurable HAMA/Lap/BMP4 hydrogel offers a therapeutic approach for scar-free wound healing. Graphical Abstract: